Determination of the Total Phenolics, Flavonoids, Phenolics and Flavonoids Profile, Vitamins and Amino Acids Profile Using HPLC and DPPH Free Scavenging Radical Acitivities of the Methanol Leaf Extract of Persea americana - Yakubu, Ojochenemi Ejeh; Otitoju, Olawale; Danjuma, Janya; Jankada, Patience Audu (Kwaghe International Journal of Sciences and Technology, 2024)
This research examined the total phenolics, flavonoids, flavonoids and phenolics profile, vitamins and amino acids profile uing HPLC as well as the DPPH free scavenging activity of methanol leaf extract of P. americana. Plants have shown to possess phytochemicals which are beneficial to man including therapeutic and disease prevention. P. americana leaves was harvested from its tree in Baissa, Taraba State. The leaves were air dried under shade at room temperature after which it was pulverized using clean mortar and pestle. The powdered sample was extracted using methanol for 72 hours. Extract was filtered using whatmann no. 1 filter paper and evaporated using rotary evaporator and water bath to obtain the required concentrate. The concentrated extract was subjected to total flavonoid and total phenolics content using aluminium chloride folin ciocaltue respectively. Total antioxidant capacity of the leaf extract was carried out using DPPH. The amino acids, vitamins, flavonoids and phenolics profiles were evaluated. The result reveals that there is a significant level of flavonoid and phenolics in the extract which accounted for 43.32±0.15 mg GAE/100g and 32.84±2.13 mg CE/100g respectively. The antioxidant capacity showed a promising inhibition of DPPH free radical scavenging activity with increase in dose. The amino acids that were found to be present in the extract include asparagine, threonine, histidine, phenylalanine and aspartic acid with different percentage. Vitamins K, B1 and B3 were detected significantly in the leaf extract. The various phytochemicals detected have shown according to research to have beneficial to the biological system, especially in scavenging free radicals and mitigation of oxidative stress. Vitamins are essential for normal functions and metabolism in the biological system, their deficiency could have deleterious effects. Amino acids are necessary for protein synthesis and are required for other biological processes. The extract has shown to be a rich source of various phytochemicals and have shown a promising presence of various vitamins and amino acids.